SELECTION OF KURAU FISHING TECHNOLOGY UNITS Eleutheronema tetradactylum WHICH COMPETITIVE AND SUSTAINABLE - Muhammad Natsir Kholis; Ronny I Wahju; . Mustaruddin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Environmentally friendly fishing technology unit is needed in sustainable fisheries management. The purpose of this study was to determine the fishing technology unit of kurau competitive and sustainable. Data collection was carried out from July to September 2016 in the Coastal Pambang of Bengkalis District of Riau Province, by using the survey method. The analytical data method used is scoring the biological, technical and socioeconomic aspects the fishing technology unit of kurau. Results of research show that combined analysis of biological, technical and socioeconomic aspects have the value of the VA fishing line function (2.48) is higher than the other three fishing gear. Thus, the fishing line is a selected fishing technology unit of kurau competitive and sustainable in the Coastal Pambang Bengkalis District. Keywords: competitive,coastal pambang, fishing technology, kurau fish,sustainable fishing